ANALYSIS OF TAKALAR GOVERNMENT POLICY IN MANAGING THE BEBA FISH LANDING BASE FROM SIYASAH SYAR'IYYAH PERSPECTIVE - Asrullah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to explain the Takalar government's policy in managing the Beba fish landing base and to examine the Takalar government's policy in managing the Beba fish landing base from the perspective of Siyasah Syar'iyyah. This research is qualitative in nature. The research design is field research. The results of this study show that the management of the Beba Fish Landing Base reflects the application of the principles of justice, public interest, and protection of individual rights. This includes involving the community in various aspects of the management of the Beba Fish Landing Base, which is in line with the principle of justice in Islam, which emphasizes the importance of siding with the interests of the wider community. Creating employment opportunities is also an important aspect of public welfare, and providing adequate infrastructure demonstrates a commitment to protecting the rights of fishermen and the community. This shows that the policies adopted by the government do not only focus on economic aspects, but also take into account social welfare and community rights, thereby providing long-term benefits for all parties. This reality shows that benefits have been achieved. This demonstrates alignment with the concept of siyasah syar'iyyah.